The Analysis of Collocations Used in The Film Entitled “Rambo: Last Blood” By Adrian Grunberg - Rosanna Marpaung; Kammer Tuahman Sipayung; Herpen Silitonga (Education Achievement: Journal of Science and Research, 2023)
The Analysis of Collocations Use the Film Entitled "Rambo: Last Blood" by Adrian Grunberg."Collocation is a combination of words in a language that occurs very often and more often than by chance. This study aimed to discover the types of collocations used in the film "Rambo: Last Blood" by Adrian Grunberg. Moreover, to find out the dominant type of Collocation in the Collocation of the film entitled: "Rambo: Last Blood" by Adrian Grunberg. This study used a qualitative descriptive method to analyze data, a collocation in the film's subtitle. The data source in this study is the subtitled transcript of the film “Rambo: Last Blood "by Adrian Grunberg, which was taken from the translation of the Netflix application. The data in this study are English collocations in the film subtitle "Rambo: Last Blood” and its translation into Indonesian in phrases. The result shows that the maximum percentage is 70% and the minimum percentage is 30%. It can be concluded that the dominant type of collocation results in the Collocation of the film entitled: "Rambo: Last Blood" by Adrian Grunberg is Lexical Collocation with a presentation result of 70%. So the dominant Collocation that was used in the film "Rambo: Last Blood" by Adrian Grunberg is Lexical Collocation (70%) because it showed a significant presence.